UPAYA PENINGKATAN HASIL BELAJAR DENGAN MENGGUNAKAN MODEL SCRAMBLE PADA MATERI GAYA PADA KELAS IV SDN 08 PANAI HILIR KECAMATAN PANAI HILIR - Tatap Mauren Siringo-Ringo (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This research aims (1) to find out whether there is an increase in student learning outcomes on Style Material by using the Scramble learning model in Class IV SDN 08 Panai Hilir (2) To find out whether teacher and student activity has increased in learning science on Style Material by using the Scramble Model . This research is Classroom Action Research. The subjects of this research were Class IV students at SDN 08 Panai Hilir, Labuhanbatu Regency with 28 students studied, with 17 male students and 11 female students. The object of this research is to improve the science learning outcomes of 28 students. Based on the research results, it can be concluded that applying the Scramble Model to Style Material is effective and can improve student learning outcomes for Class IV students at SDN 08 Panai Hilir. In the initial test, there were 13 students (46.43%) who had achieved an individual learning completion level of ≥ 60%, while 15 students (53.57%) had not achieved an individual learning completion level of ≤ 60% and an average score of 55. 36%. In cycle I, there were 20 students (71.43%) who had reached the level of individual learning completeness, while 8 students (28.57%) had not reached the level of learning completeness and the average score of student learning outcomes in cycle I was 62. 14%. The increase in learning completeness reached 25.00%, while the increase in class average ability reached 6.78%. In cycle II, there were 25 students (89.29%) who had reached the level of individual learning completeness, while 3 students (10.71%) were still incomplete and the average student learning outcome score was 82.14%%. The increase in learning completeness reached 17.86%, while the increase in class average ability reached 20.00%. Teacher observations in cycle I reached 66.67% and in cycle II reached 89.58%, resulting in an increase of 22.91%. Meanwhile, student observations in cycle I reached 65.00% and in cycle II reached 85.00%, resulting in an increase of 20.00%.